Learning during the Pandemic: Evidence from Uzbekistan - Syedah Aroob Iqbal; Harry A. Patrinos (Institute of Labor Economics (IZA), 2023)
School closures induced by the COVID-19 pandemic led to concerns about student learning. This paper evaluates the effect of school closures on student learning in Uzbekistan, using a unique dataset that allows assessing change in learning over time. The findings show that test scores in math for grade 5 students improved over time by 0.29 standard deviation despite school closures. The outcomes among students who were assessed in 2019 improved by an average of 0.72 standard deviation over the next two years, slightly lower than the expected growth of 0.80 standard deviation. The paper explores the reasons for no learning loss.
Keywords: I21; I24; 330; COVID-19; learning loss; school closures; social inequality; digital divide